BIOFUEL PRODUCTION FROM PALM OLEIN BY CATALYTIC CRACKING PROCESS USING ZSM-5 CATALYST - Tambun, Rondang; Gusti, Oktris Novali; Nasution, Muhammad Anshori; Saptawaldi, Rangga Pramana (Jurnal Bahan Alam Terbarukan, 2017)
The depletion of fossil energy reserves raises the potential in the development of renewable fuels from vegetable oils. Indonesia is the largest palm oil producer in the world, where palm oil can be converted into biofuels such as biogasoline, kerosene and biodiesel. These biofuels are environmentally friendly and free of the content of nitrogen and sulfur through catalytic cracking process. In this research, palm olein is used as feedstock using catalytic cracking process. ZSM-5 is used as a catalyst, which has a surface area of 425 m2/g and Si/Al ratio of 50. Variables varied are the operating temperature of 375 oC - 450 Â°C and reaction time of 60 minutes - 150 minutes. The result shows that the highest yield of liquid product is 84.82%. This yield is obtained at a temperature of 400 Â°C and reaction time of 120 minutes. The yield of the liquid product in the operating conditions consisting of C6-C12 amounted to 19.47 %, C14-C16 amounted to 16.56 % and the C18-C28 amounted to 48.80 %.